Regional variations in mortality from ischaemic heart and cerebrovascular disease in Britain. Issue 5 (May 1978) - Fulton, M; Adams, W; Lutz, W; Oliver, M F
Abstract : In middle-aged men and women, mortality from ischaemic heart disease and cerebrovascular disease is highest in the north and west of Britain. The worst region is West Central Scotland. Statistical analysis using a linear logistic model shows that the differences between the regions are significant and the yearly fluctuation in numbers of deaths contributes little to the overall variation.